Investigating the Mechanism of the Effect of Nature-based Architectural Components on Residential Satisfaction - Azizibabani, Mohammadhossein; Bemanian, Mohammadreza; Yeganeh, Mansour (FormAkademisk, 2023)
The development of multi-unit urban housing, especially in the metropolises of Iran, does not take into account the effects of cultural factors on the perceived quality of housing architecture. Since the community is diverse in metropolises, especially on a sub-culture scale, it is impossible to provide housing development strategies and practical actions concerning the factors related to this scale of culture. The compatibility of lifestyle at the national or structural level with housing can be considered a general strategy to solve this problem. Based on the position of nature in the foundations of the Islamic lifestyle, it is possible to accommodate humans’ significant needs through inspiration from nature. This paper intends to investigate the mechanism of the effect of nature-based architectural components (NBAC) on residential satisfaction (RS) from the Islamic lifestyle perspective to apply the findings in architectural planning and programming processes. The results demonstrate that as adherence to the Islamic lifestyle increases, residential preferences related to the formal and semantic dimensions of NBAC also increase. Qualitative deficiencies in these components cause a decrease in perceived quality and, consequently, RS. Therefore, high residential preferences regarding semantic and formal components lead to the intensification of deficiencies in qualitative perception. In such conditions, a large part of the RS is due to residents’ adaptive behaviors. Therefore, measuring RS based on accommodating residential needs cannot be considered an objective criterion to determine housing architecture quality to test the fit of housing development patterns with residential needs. This proves the necessity for the measurement of the perceived quality of housing architecture based on the main influential factors involved, which are NBAC.